Brain diseases and aspiration pneumonia in older person. Issue 1 (30th November 2021) - Sakakibara, Ryuji; Iimura, Ayako; Ogata, Tsuyoshi; Terayama, Keiichiro; Katsuragawa, Shuichi; Nagao, Takaaki; Suzuki, Keiko; Izawa, Kaori; Nakajima, Kiwa; Haruki, Shinichi; Okada, Nobuyuki; Sawai, Setsu; et al.
Abstract: Objective: Age‐related brain symptoms (gait, speech and swallowing difficulties, and dementia) increase the risk of aspiration pneumonia (AP). It is not known which types of brain disease underlie AP most closely. Our neurogeriatric team addressed this issue herein. Patients and Methods: We retrospectively analyzed the cases of in‐patients diagnosed with AP at our multi‐faculty university hospital within a 12‐month recruiting period, with a 3.0 ± 2.5‐week follow‐up and ≥1×/week visits. We determined the patients' organic and neural disorders with neuroimaging to the extent possible. Results: The AP patients (n = 136) were generally old (mean age 75 years, range 3‐98 years) and male‐dominant (81 males, 55 females). All patients showed gait and attention/cognitive problems at admission, suggestive of encephalopathy/delirium. They were treated in 11 hospital wards: neurology (N) or non‐N (ratio 1:1.3). The ratio of organic disorders (esophageal carcinoma, etc) vs neural disorders was 1:30. Most of the neural disorders were age‐related brain diseases, eg, a combination of white matter disease (WMD) and Alzheimer's disease (AD), followed by dementia with Lewy bodies (DLB). In total, they were WMD in 111, AD in 102, DLB in 20. Conclusion: A combination of premorbid age‐related brain diseases (a combination of WMD and AD, DLB, etc) with encephalopathy/delirium (and intrinsic brain diseases) might lead to AP.